Mexico's bravest man - Minn, Charlie; Dreamscape Media; Charlie Minn Films (Firm); Soundview Media Partners ([United States] : Charlie Minn Films, 2016)
After Julian Leyzaola Perez declared open war on the drug cartels, murder rates dropped, but outrage spilled over regarding human rights abuses committed by the police.
Originally released as a motion picture in 2016.
Adriana Allende, Jesus Antonio Castaneda Alvarez, Edward Benavides.
Cinematographers, Juventino Mata, Cesar Ruiz ; editor, Marvin Yoda ; music, Kyle Hildenbrand.
In English and Spanish; subtitles in English for Spanish dialogues.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed February 12, 2020)
Keywords: Leyzaola, Julián, -- 1960-; Police chiefs -- Mexico; Drug dealers -- Mexico; Drug traffic -- Mexico; Human rights -- Mexico; Documentary films; Nonfiction films; Internet videos; Streaming video